The Russian Revolution, the Famine of 1921-1923, and the International Humanitarian aid - Bouroutis, Andreas (Mos Historicus: A Critical Review of European History, 2024)
After a three-year struggle starting with the Revolution of 1917, the Bolsheviks consolidated their power in Russia. Due to the collapse of the economy and the need to support urban populations, the requisition of grain was imposed on the rural areas. This soon escalated into the massive confiscation of the peasants’ production. Conditions further deteriorated in 1921, following two consecutive years of crop failure, plunging the country into a famine that caused tens of thousands of deaths. Unable to provide a solution, the Bolsheviks petitioned for international aid. Thus, despite the revolutionaries’ reservations, the American Relief Administration (ARA) actively operated in Russia from 1921 to 1923. At the peak of its activity, ARA was feeding more than 10 million Russians. This article analyzes the course of the revolution, from its establishment to the emergence of the humanitarian catastrophe, as well as the characteristics of the activity of ARA and other humanitarian organizations in Soviet Russia.